Investigation of the influence of “Pear powder” food additive on the quality and properties of wheat flour - E. P. Victorova; O. V. Fedoseeva; T. A. Shakhray; E. V. Velikanova; A. N. Matvienko; E. E. Dikolova (Новые технологии)
The results of the research on the effect of “Pear Powder” food additive on the quality and properties of first grade wheat flour are presented. It’s been determined that adding of the investigated food additive to the first grade wheat flour has a strengthening effect on gluten flour, which converts the gluten flour from quality group II to quality group I. It is shown that adding food additive to wheat flour provides an increase in its gas-forming ability, that is due to the presence of sugars, minerals and organic acids in the additive, that contribute to the intensification of the gassing process.